Three Weeks on a Ketogenic Diet Reduces Free Testosterone and Free Estradiol in Middle-Aged Obese Men and Women - Mads Svart; Nikolaj Rittig; Thien Vinh Luong; Nigopan Gopalasingam; Esben Thyssen Vestergaard; Lars Gormsen; Esben Søndergaard; Henrik Holm Thomsen; Claus H. Gravholt (Journal of Nutrition and Metabolism)
Background. Beta-hydroxybuturate (β-OHB) supplements are commonly utilized in sports by both recreational and professional athletes. In a recent study, we observed a drop in testosterone levels following the oral ingestion of racemic sodium-β-OHB. In this investigation, we aim to determine whether a single oral dose of ketone ester (study I) and prolonged endogenous ketosis (study II) also reduces testosterone levels. Design. This investigation integrated samples from two distinct studies. Study I was a randomized, controlled, crossover trial with ten healthy, young male participants receiving either a weight-adjusted ketone ester or control (water, CTR) and vice versa following an overnight fast. Repeated blood sampling was used to monitor plasma β-OHB and testosterone levels. Study II, another randomized, controlled, crossover trial, included 11 middle-aged participants (five males). They followed either a ketogenic diet (KD) characterized by low carbohydrates and high fat content or a standard diet (SDD) for three weeks. After each study period, participants underwent examination following an overnight fast, with repeated measures employed to analyze concentrations of plasma β-OHB and sex hormone levels. Results. Study I: Testosterone decreased from 23.8 ± 2.4 nmol/l to 22.3 ± 2.5 nmol/l 300 minutes after the ketone ester and increased from 20.9 ± 2.1 nmol/l to 22.2 ± 1.9 300 minutes after CTR. This difference was not significant, p = 0.06. Study II. Total testosterone was unaffected after the KD compared to the SDD in men (20.2 ± 1.23 nmol/l vs. 18.2 ± 1.23 nmol/l (p = 0.1)) and was lower after KD in women (0.87 ± 0.06 vs. 1.1 ± 0.06 nmol/l (p < 0.0001)). Sex hormone-binding globulin (SHBG) increased in men after KD compared with SDD (31.2 ± 2.6 nmol/l vs 25.0 ± 2.6 nmol/l, p < 0.0001) and women (26.5 ± 3.05 nmol/l vs 24.2 ± 3.05 nmol/l, p = 0.003). The free androgen index decreased after KD in men (ratio: 0.65 ± 0.05 vs. ratio: 0.74 ± 0.05, p = 0.04) and in women (ratio: 0.036 ± 0.006 vs. SDD 0.05 ± 0.006, p = 0.0001). Free estradiol index was also found lower after KD in men (ratio: 3.1 ± 0.8 vs. ratio: 4.8 ± 0.8, p = 0.0003) and in women (ratio: 1.2 ± 2.2 vs. 9.8 ± 2.2, p = 0.0001). Conclusion. Our findings indicate that the acute ingestion of ketone ester may not reduce testosterone levels in healthy young males. However, a three-week exposure to KB from a KD results in an increase in SHBG in men and women with obesity as well as it lowers free testosterone and estradiol for men and women. We thus present evidence of crosstalk between alterations in a metabolite, β-OHB, and the regulation of the hypothalamic-pituitary-gonadal axis from a KD. The clinical impact of this reduction remains to be investigated. This trial is registered with NCT04156477​ and NCT05012748.